2012
DOI: 10.1007/s13593-012-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry and biochar to offset climate change: a review

Abstract: Expansion of agricultural land use has increased emission of greenhouse gases, exacerbating climatic changes. Most agricultural soils have lost a large portion of their antecedent soil organic carbon storage, becoming a source of atmospheric carbon-dioxide. In addition, agricultural soils can also be a major source of nitrous oxide and methane. Adoption of conservation agricultural practices may mitigate some of the adverse impacts of landuse intensification. However, optimal implementation of these practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(97 citation statements)
references
References 72 publications
(86 reference statements)
2
83
1
1
Order By: Relevance
“…Farm and food system issues: sustainable intensification, agroecosystem management and food systems Considerable research on climate change and agriculture exists at the farm and food system levels, including topics such as farming practices for mitigation of agricultural GHG emissions, choice and adaptation of crops and livestock to new climate regimes, decision-making by farmers and life-cycle assessments [51][52][53][54][55]. The tendency has been to apply disciplinary science that informs particular problems and solutions for agriculture, as demonstrated by the topics of the six sessions in theme 1.…”
Section: Themementioning
confidence: 99%
“…Farm and food system issues: sustainable intensification, agroecosystem management and food systems Considerable research on climate change and agriculture exists at the farm and food system levels, including topics such as farming practices for mitigation of agricultural GHG emissions, choice and adaptation of crops and livestock to new climate regimes, decision-making by farmers and life-cycle assessments [51][52][53][54][55]. The tendency has been to apply disciplinary science that informs particular problems and solutions for agriculture, as demonstrated by the topics of the six sessions in theme 1.…”
Section: Themementioning
confidence: 99%
“…Among the important aspects of these practices is the decreased disturbance to the structure of the uppermost soil layers (Stavi and Lal 2012). This is achieved through the simultaneous adoption of two essential farm practices: a reduced tillage method of seedbed preparation and permanent soil cover through crop residue management (mulching).…”
Section: Minimum Soil Disturbancementioning
confidence: 99%
“…Produced by the thermochemical conversation of organic residues in an oxygen-limited environment [2], biochar is highly resistant to degradation due to recalcitrant carbon, and it has the potential to improve soil quality [3]. The addition of biochar has been documented to alter the soil porosity, moisture content, pH, labile C and N pool sizes, which would markedly impact soil CO 2 emissions [4,5]. However, previous studies have shown that biochar addition with different rawmaterials and different soil textures can have different effects (an increase, decrease or no effect) on the CO 2 flux in the laboratory or field experiments [6][7][8].…”
Section: Introductionmentioning
confidence: 99%